Wednesday

April 16, 2014

April 16, 2014

Posted by **Shreya** on Monday, January 9, 2012 at 10:13am.

5y/(2y-3)(3y+1)+(4y-3)(2y-3)(y-6)

i not get what it asking for.

- math-calculus -
**Reiny**, Monday, January 9, 2012 at 10:35am5y/( (2y-3)(3y+1) )+(4y-3)/((2y-3)(y-6) )

look at the denominators .

We know we cannot divide by zero, so the "nonpermissible" values of x would be all those that make either one of the denominators zero.

But you factored it, so that is good, all we have to find out which values make any of the factors equal to zero

so.....

2y-3 ≠ 0

2y ≠ 3

y ≠ 3/2

3y+1 ≠ 0

3y ≠ -1

y ≠ -1/3

and

y ≠ 6

so the nonpermissible values of x are -1/3, 2/3 and 6

- math-calculus -
**Shreya**, Monday, January 9, 2012 at 10:48amthanks very much reiny :)

**Related Questions**

algebra--distributive - how would you do this prob. negative4-(5y+6) = negative ...

Expressions help - I have no idea on how to do this equation please help me. ...

Algebra - To solve the system of equations, which expression could be ...

math - 3y+6y^3-2y^2+5y^3+5y^2-4y+2

math - 3y+6y^3-2y^2+5y^3+5y^2-4y+2

Algebra 2 - Solve the system using any algebraic method. 22.)2x-5y=4 23.)5x+7y=...

Math - Solve the system by addition or substitution. 3x – 4y = 8 6x – 2y = 10 ...

mATH, ALGEBRA - i need help solving the system by addition. 5x-7y=5 x+3y=1 this ...

math - pls help me to solved this equation 1. 6y=x+18 2y-x=6, 2. 4x=3y=13 2x-4y=...

math - -5y^3(y-6)+4y^3(y-7) OK - first, distribute -5y^3 to the (y-6). You ...